The role of the exogenous supply of adenosine triphosphate in the expression of Bax and Bcl2L1 genes in intestinal ischemia and reperfusion in rats - Fagundes,Djalma José (2018)
Abstract Purpose: To investigate the role of the exogenous supply of adenosine triphosphate (ATP) in the expression of Bax and Bcl2L1 genes in intestinal ischemia and reperfusion (IR) in rats. Methods: The study was designed as a randomized controlled trial with a blinded assessment of the outcome. Eighteen adult male Wistar-EPM1 rats were housed under controlled temperature and light conditions (22-23°C, 12 h light/dark cycle). The animals were randomly divided into 3 groups: 1. Sham group (SG): no clamping of the superior mesenteric artery; 2. Ischemia and reperfusion group (IRG): 3. Ischemia and reperfusion plus ATP (IRG + ATP). ATP was injected in the femoral vein before and after ischemia. Afterwards, intestinal segments were appropriately removed and processed for Endothelial Cell Biology Rat RT2 Profiler PCR Array. Results: ATP promoted the upregulation of Bcl2L1 gene expression, whereas it did not have significant effects on Bax gene expression. In addition, the relation of Bax/Bcl2L1 gene expression in the IRG group was 1.39, whereas it was 0.43 in the IRG + ATP group. Bcl2L1 plays a crucial role in protecting against intestinal apoptosis after ischemia and reperfusion. Increased Bcl2L1 expression can inhibit apoptosis while decreased Bcl2L1 expression can trigger apoptosis. Conclusion: Adenosine triphosphate was associated with antiapoptotic effects on the rat intestine ischemia and reperfusion by upregulating of Bcl2L1 gene expression.